Planning the capitalist city : the colonial era to the 1920s - Foglesong, Richard E., 1948- (Princeton legacy library, 1986)
Starting with the colonial period, but focusing especially on the Progressive era, Richard Foglesong offers both a narrative account and a theoretical interpretation of urban planning in the United States. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.